Manejo da adubação na cultura do feijão em sistema de produção orgânico - Pereira, Leandro Barradas [UNESP]; Arf, Orivaldo [UNESP]; Santos, Neli Cristina Belmiro Dos; Oliveira, Aline Estela Zini De; Komuro, Lauro Kenji (Escola de Agronomia e Engenharia de Alimentos/UFG, 2015)
Nowadays the food production systems tend to include the sustainable management of soil and water. One of the main obstacles to the organic cultivation of common bean is the fertilization management. This study aimed to evaluate doses of organic fertilizer containing slaughterhouse residues (1.0 t ha-1, 1.5 t ha-1, 2.0 t ha-1 and 2.5 t ha-1). The experimental design was randomized blocks in a 4x2x2 factorial scheme, with 16 treatments and 4 replications. Plant dry weight; foliar diagnose; initial and final plant population; number of pods per plant, grains per plant and grains per pod; 1000-grain weight; and grain yield were evaluated. It was concluded that the methods and time of organic fertilizer application do not affect the production components and yield in common bean. The dose of 2.5 t ha-1 of organic fertilizer provided the highest common bean yield in 2012, but it did not express its maximum production capacity.

Atualmente, os sistemas de produção de alimentos tendem a incluir manejos sustentáveis do solo e da água. Um dos principais desafios do cultivo orgânico do feijoeiro é o manejo da adubação. Este trabalho objetivou avaliar doses de fertilizante orgânico à base de resíduos de frigorífico (1,0 t ha-1; 1,5 t ha-1; 2,0 t ha-1; e 2,5 t ha-1). O delineamento experimental foi em blocos casualizados, em esquema fatorial 4x2x2, com 16 tratamentos e 4 repetições. Foram realizadas as seguintes avaliações: massa seca de plantas; diagnose foliar; população inicial e final de plantas; número de vagens por planta, grãos por planta e grãos por vagem; massa de 100 grãos; e produtividade de grãos. Concluiu-se que os métodos e épocas de aplicação do fertilizante orgânico não influenciam os componentes de produção e produtividade do feijoeiro. A dose de 2,5 t ha-1 de fertilizante orgânico propiciou a maior produtividade do feijoeiro em 2012, porém, não expressou sua capacidade máxima de produção.
Fertilization management in bean crop under organic production system
Keywords: Phaseolus vulgaris L.; organic fertilizer; cattle residues; Phaseolus vulgaris L.; fertilizante orgânico; resíduos bovinos